Recurrent Self-Induced Nontraumatic Orbital Emphysema Causing Orbital Compartment Syndrome with Optic Nerve Dysfunction - S. Cutting; C. Davies-Husband; C. Poitelea (Case Reports in Ophthalmological Medicine)
The majority of cases of orbital emphysema are due to trauma. Complications are rare, and therefore, the need for surgical intervention is uncommon. We present the first case of which we are aware in which nontraumatic orbital emphysema led to orbital compartment syndrome and subsequent optic nerve dysfunction. The patient underwent emergency needle decompression. A 51-year-old man presented to the Emergency Department with right-sided unilateral proptosis, reduced visual acuity, and binocular diplopia. This occurred after performing a Valsalva manoeuvre with no history of head trauma. He also mentioned that over the past year he had experienced multiple episodes of transient proptosis occurring after Valsalva manoeuvres. Visual acuity in the right eye was reduced to 6/21. A relative afferent pupillary defect was present and intraocular pressure (IOP) was 12 mmHg. The CT scan showed significant orbital emphysema in the medial aspect of the right orbit. Needle decompression was performed resulting in immediate resolution of his symptoms. This case demonstrates that, in cases of orbital emphysema, a lack of a history of trauma and a normal IOP cannot always be used to rule out serious pathology.